Çok katlı bir yapının statik ve betonarme hesapları - Belene, Duran (Fen Bilimleri Enstitüsü, 1995)
Yüksek lisans tezi olarak sunulan bu çalışmada çok katlı bir betonarme yüksek bina projelendirilmiştir. Yapı, Şekil 1.1 de de görüldüğü gibi plandaki boyutları 29.65 * 21.20 metre ve temelden yüksekliği 58.80 m. olan ve toplam 21 kattan oluşan konut amacıyla tasarlanmış betonarme bir binadır. Ele alınan yapının 1. derece deprem bölgesinde yer aldığı düşünülmüş ve taşıyıcı sisteminin seçiminde bu husus ile birlikte yüksek yapı olması durumu gözönünde bulundurularak betonarme perde duvarlardan oluşan; bir panel taşıyıcı seçimine gidilmiştir. Bu taşıyıcı sistemin seçimindeki diğer bir sebep ise kalıp kolaylığı ve zamandan tasarruftur. Yapı 1. derece deprem bölgesinde olduğu için dinamik hesap yapılmıştır. Kesit hesaplan, Kaynak [2] ’ye uygun olarak taşıma gücü yöntemi esas alınarak yapılmıştır. Aksların düzenli ve açıklıkların az olması sebebiyle döşeme sistemi olarak kirişsiz plak döşeme seçilmiştir. İkinci bölümde yeralan bu hesaplarda önce döşeme kalınlıkları sehim hesabı gerektirmeyecek şekilde beMenmiş daha sonra sistem içerisinde yer alan tıîrn döşemelerin yük analizleri Kaynak [3]’e göre ayn ayrı yapılmış ve elde edilen yüklere göre döşemelerin statik ve betonarme hesapları, sonlu elemanlar yöntemine göre plak ve kabuk türü elemanların hesabını yapan SAFE programı ile yapılmıştır. Üçüncü bölümde yapının yatay yüklere göre statik ve dinamik analizi perdeli yapılar için uğun bir program olan ETABS programı ile yapılmıştır. Dinamik analizde herbir farklı kat döşemesindeki alan ve şerit yükler seçilen bir global eksen takımına göre yük ve koordinat değerleri ile birlikte ayn ayn girilmiş ve girilen bu ağırlık emsinden yükler program tarafından kütleye çevrilmiş ve sistemin kütle ve rijitlik merkezleri program tarafından bulunmuştur. Kütle özelliklerinin belirlenmesinden sonra taşıyıcı sistem içerisinde yer alan elemanların kesit özellikleri programa verilmiştir. Daha sonra seçilen global eksen takımına göre yapmın taşıyıcı sistemini oluşturan elemanlan belirtmek amacıyla düşey kolon akslan tariflenmiştir. Bundan sonra panel ve kiriş elemanların tariflenen kolon akslarına göre yerleştirimi yapılarak yapmm 3 boyutlu modeli kurulmuştur. Dördüncü bölümde döşemelerden perdelere aktarılan yükler bulunmuş ve perdelerde düşey yüklerden oluşan normal kuvvetler elde edilmiştir. Beşinci bölümde perdelerde yatay dinamik anliz sonuçlan ile düşey analiz sonucunda elde edilen kesit tesirleri süperpozisyonlan yapılmışta-. Elde edilen maksimum kesit tesirlerine göre perdelerin donatı hesaplan önce bir tanesi el ile diğerleri ise BIAXIAL betanarme programı ile yapılmışta. Altıncı bölümde perde bağ kirişlerinin hesabı Kaynak [7] ’ye göre taşıma gücü yöntemine uygun olarak yapılmışta. Yedinci bölümde merdiven statik ve betonarme hesabı yapılmışta. Sekizinci bölümde temel sistemi, radye temel olarak seçilmiş ve statik ve betonarme hesaplan SAFE programı ile yapılmışta.

The design project of a multi-storey reinforced concrete building is presented herein as a master thesis. The building as shown in Figure 1.1 which will be used as a residence, is 58.80 meter high from the foundation level and is 29.65 x 21.20 meter planewise. It has 2 1 floors. The load carrying system consists of shear walls. A dynamic analysis was performed since the building is tall and located in the first zone of the earthquake map. The results from the dynamic analysis are compared with those obtained from the static analysis. Another advantage of such a system is easy to construct in a reasonable time period. The design starts with slab calculations. The slab calculations are presented in Chapter 2. The slab is designed as a plate because the spans in the system are shorts. The load analysis of the slab is in accordence with the Turkish Standard TS 498 Reference [ 3 ]. The slab thickness is first determined in such a way that no deflection calculation is necessary. Then the load analysis is done for each different slab ( normal floors, roof and machine room floor ). And from the obtained loads, the design calculations are performed by means of the program SAFE that uses the finite element method. Before using the SAFE program, the slab is devided into segments. Gridlines define segments. Then the structural element ( beam, slab, support ) properties are calculated and entered in the program together with their locations. Another data is the load acting on the slab( live load and dead load ). Loads are entered in three different ways which are point loads, line loads ( walls ) and surface loads ( live loads and dead loads ). Since the system is symetricaL only half of the slab system is analysed. In the design of reinforcement, the design loads are multiplied by load factors which are input externally. Since the roof and machine room floors are similar to normal floors, then- design calculations are not included here. The only slab design calculations to be included here is the normal floor design calculation. In order to save time and manpower involved in the construction of this structure, the mesh reinforcement is used. Additional reinforement is used along holes and also along the edges according to the code. Chapter 3 includes both the dynamic and the static calculations due to the horizontal loads. A dynamic analysis is performed since the building considered is a tall one and located in the first earthquake zone. Since the building is located in the first zone of earthquake map, the panel load carrying system consisting of shear walls is choosen. vin forces from the dynamic analysis are superimposed with the forces from the vertical analysis. The program SAFE is used in the calculation of the foundation slab. The vertical loads from the superstructure are entered in the program as line loads. The shear wall end-moments are entered as pressures. The foundation design calculations are based on the Turkish Code TS 500. Various load combinations are used in the calculations and the corresponding reinforcements are choosen. The foundation area is found to be correct since the maximum pressure is less than the allowable soil pressure. The top and bottom reinforcements are $16/15 in both directions according to the minimum reinforcement requirement. Additional reinforcement is used whereever necessary. xm the flexural reinforcement. For small span / depth ratios, tensile stress will exist in the reinforcement at locations in which conventional flexural theory indicates that compression stresses should be present. When insufficient web reinforcement is provided, the stirrups will yield, and a much greater degree of stiffness degradation ensues. This is particularly noticeable when small loads are applied in a new load cycle. Large rations occur before the previously opened diagonal cracks close, permitting the newly formed diagonal copression to be transmitted. Because the top and bottom reinforcement is in tension over the full clear span of a coupling beam when L / h < 1.5, the beam becomes longer during inelastic loading cyclies. All intermediate bars, distributed over the depth of the beam, are thus strained, and they contribute toward the strength of the beam. The total tension force generated in all the horizontal reinforcement is approximately constant over the span, and the internal compression must therefore act along a diagonal If elongation of the steel occurs, the two coupled walls in a multistory structure are pushed apart. The ductility and useful strength of coupling beams can be cosiderably improved if instead of the previously described conventional steel arrangement, the principal reinforcement is placed diagonally in the beam. The design of such a beam can be based on the premise that the shearing force resolves itself into diagonal copression and tension forces, intersecting each other at midspan where no moment is to be resisted. Initially the diagonal compression is transmitted by the concrete, and the compression steel makes an insignificant contribution. After the first excursion of the diagonal tension bars into the yield range, however, large cracks form and remain open when the load is removed. When the reserved load is applied, as during an earthquake, these bars are subjected to large compression stress, perhaps yielding, before the previously formed cracks close. Since equal amounts of steel are to be provided in both diagonal bands, the loss of the contribution of the concrete is without consequence, provided the diagonal compression bars do not become unstable. For seismic-type loading it is therefore important to have ample ties arround the diagonal compression bars, to retain the concrete arround the bars. The main purpose of the retained concrete is to furnish some lateral flexural rigidity to to the diagonal strut, thus to enable compression yielding of the main diagonal bars to take place. Because the concrete, apart from stabilizing the compression bars, has no influence on the behaviour of diagonally reinforced coupling beams, no degradation in strength or stiffness is to be expected during alternating cyclic loading that imposes moderate ductility. The diagonal reinforcement is used even when the anchorage length the flexural reinforcement is present or even when the ratio of length to height is between 1 and 1.5. Chapter 7 includes the stair calculation. The stair is considered as a simply suppoted beam. The stairplatform static calculation is performed using the table prepared for the plate calculations^ Reference [ 8 ] ) Chapter 8 is about the foundation calculation ( Reference [ 9 ] ). The soil is assumed to be a compacted gravel and the soil allowable pressure is taken as 400 kN / m2, the soil upgrade reaction coefficient is 280000 kN / m3. The foundation is a mat foundation because the stable layer is very near of the surface and the building is tall The forces acting on the foundation are those obtained from the shear wall analysis under the action of both vertical and horizontal forces. The cross-section XII forces from the dynamic analysis are superimposed with the forces from the vertical analysis. The program SAFE is used in the calculation of the foundation slab. The vertical loads from the superstructure are entered in the program as line loads. The shear wall end-moments are entered as pressures. The foundation design calculations are based on the Turkish Code TS 500. Various load combinations are used in the calculations and the corresponding reinforcements are choosen. The foundation area is found to be correct since the maximum pressure is less than the allowable soil pressure. The top and bottom reinforcements are $16/15 in both directions according to the minimum reinforcement requirement. Additional reinforcement is used whereever necessary. xm the flexural reinforcement. For small span / depth ratios, tensile stress will exist in the reinforcement at locations in which conventional flexural theory indicates that compression stresses should be present. When insufficient web reinforcement is provided, the stirrups will yield, and a much greater degree of stiffness degradation ensues. This is particularly noticeable when small loads are applied in a new load cycle. Large rations occur before the previously opened diagonal cracks close, permitting the newly formed diagonal copression to be transmitted. Because the top and bottom reinforcement is in tension over the full clear span of a coupling beam when L / h < 1.5, the beam becomes longer during inelastic loading cyclies. All intermediate bars, distributed over the depth of the beam, are thus strained, and they contribute toward the strength of the beam. The total tension force generated in all the horizontal reinforcement is approximately constant over the span, and the internal compression must therefore act along a diagonal If elongation of the steel occurs, the two coupled walls in a multistory structure are pushed apart. The ductility and useful strength of coupling beams can be cosiderably improved if instead of the previously described conventional steel arrangement, the principal reinforcement is placed diagonally in the beam. The design of such a beam can be based on the premise that the shearing force resolves itself into diagonal copression and tension forces, intersecting each other at midspan where no moment is to be resisted. Initially the diagonal compression is transmitted by the concrete, and the compression steel makes an insignificant contribution. After the first excursion of the diagonal tension bars into the yield range, however, large cracks form and remain open when the load is removed. When the reserved load is applied, as during an earthquake, these bars are subjected to large compression stress, perhaps yielding, before the previously formed cracks close. Since equal amounts of steel are to be provided in both diagonal bands, the loss of the contribution of the concrete is without consequence, provided the diagonal compression bars do not become unstable. For seismic-type loading it is therefore important to have ample ties arround the diagonal compression bars, to retain the concrete arround the bars. The main purpose of the retained concrete is to furnish some lateral flexural rigidity to to the diagonal strut, thus to enable compression yielding of the main diagonal bars to take place. Because the concrete, apart from stabilizing the compression bars, has no influence on the behaviour of diagonally reinforced coupling beams, no degradation in strength or stiffness is to be expected during alternating cyclic loading that imposes moderate ductility. The diagonal reinforcement is used even when the anchorage length the flexural reinforcement is present or even when the ratio of length to height is between 1 and 1.5. Chapter 7 includes the stair calculation. The stair is considered as a simply suppoted beam. The stairplatform static calculation is performed using the table prepared for the plate calculations^ Reference [ 8 ] ) Chapter 8 is about the foundation calculation ( Reference [ 9 ] ). The soil is assumed to be a compacted gravel and the soil allowable pressure is taken as 400 kN / m2, the soil upgrade reaction coefficient is 280000 kN / m3. The foundation is a mat foundation because the stable layer is very near of the surface and the building is tall The forces acting on the foundation are those obtained from the shear wall analysis under the action of both vertical and horizontal forces. The cross-section XII forces from the dynamic analysis are superimposed with the forces from the vertical analysis. The program SAFE is used in the calculation of the foundation slab. The vertical loads from the superstructure are entered in the program as line loads. The shear wall end-moments are entered as pressures. The foundation design calculations are based on the Turkish Code TS 500. Various load combinations are used in the calculations and the corresponding reinforcements are choosen. The foundation area is found to be correct since the maximum pressure is less than the allowable soil pressure. The top and bottom reinforcements are $16/15 in both directions according to the minimum reinforcement requirement. Additional reinforcement is used whereever necessary.
Design calculations of a multi-storey reinforced concrete systems
Tez (Yüksek Lisans) -- İstanbul Teknik Üniversitesi, Fen Bilimleri Enstitüsü, 1995
Keywords: Betonarme hesapları; Statik hesap yöntemleri; Yüksek yapılar; Reinforced concrete calculation; Static calculation methods; High structures